Jihad in the Qur'an: A Comparative Study of the Interpretations of Sayyid Quthb and M. Quraish Shihab - Ilham Taufiq Rohman; Yeti Dahliana (Lembaga Yasin AlSys, 2026)
Jihad represents an important concept in Islamic teachings and is generally understood as struggle in the way of Allah to uphold and strengthen Islam. However, jihad is not limited to warfare; it may also involve the sacrifice of wealth and life, as well as efforts through preaching. This article examines the concept of jihad in the Qur’an by comparing the interpretations of Sayyid Quthb in Fi Zilalil Qur’an and M. Quraish Shihab in Al-Misbah. The study aims to understand how jihad is interpreted in these two exegetical works. Using a qualitative library research method, the study analyzes the views of Sayyid Quthb and M. Quraish Shihab in interpreting Qur’anic verses related to jihad, supported by relevant books, journal articles, and previous studies. The findings indicate that, according to Sayyid Quthb, jihad is a form of struggle to liberate human beings from all forms of servitude to anything other than Allah. In contrast, Quraish Shihab interprets jihad as an effort to achieve victory, sincerity in struggle, and goodness through the use of knowledge, reason, and energy. This study contributes to Qur’anic interpretation studies by highlighting the conceptual differences between two influential exegetes in understanding jihad. It also provides a broader perspective on jihad as a multidimensional concept that extends beyond armed struggle and includes intellectual, spiritual, and moral efforts.